Academic vascular unit collaboration with advertising agency yields higher compliance in screening for abdominal aortic aneurysm. (December 2014) - Zarrouk, Moncef; Gottsäter, Anders; Malina, Martin; Holst, Jan
To improve compliance with abdominal aortic aneurysm (AAA) screening in low compliance areas, individually tailored invitations were developed in collaboration with a professional advertising agency. Compliance increased in two intervention municipalities from 71.4% in 2010–2012 to 78.1% in 2013 (p = 0.025), and was then higher [odds ratio 1.7; 95% confidence interval 1.1–2.6; p = 0.013] than in two control municipalities in which compliance was unchanged (417/552 [75.5%] in 2010–12 and 122/180 [67.8%] in 2013). Compliance with AAA-screening can be increased by collaboration with a professional advertising agency, albeit at a comparably high cost.